TREATMENT EFFORTS IN CHILDREN WITH READING DIFFICULTY CLASS IV AT MAJAH 2 BANGKALAN ELEMENTARY SCHOOL - Bekiyatus Solehah; Isna Ida Mardiyana; Astien Diena Koesmini; Rukmiyati Rukmiyati (Citra Dharma Cindekia, 2022)
The purpose of this study include the know: 1) To find out the factors that cause children to have difficulty reading (Dyslexia) in class IV Mlajah 2 Elementary School, 2) To find out what efforts are made by teachers and parents to overcome reading difficulties ( Dyslexia) student IV Mlajah 2 Elementary School. This study uses a qualitative approach to the type of case study research. Data collection techniques used in this study were observation, interviews, and documentation. The results of the study show that: 1) The teaching and learning process in class IV of Mlajah 2 Elementary School has been going well. factors that cause reading difficulties (Dyslexia) in students include intelligence factors, very dense curriculum, high expectations of teachers and parents and lack of attention and cooperation from the family towards the child's learning process. 2. Efforts to overcome reading difficulties (dyslexia) in class IV of Mlajah 2 Elementary School namely, by providing additional tutoring outside of class hours and the use of various varied methods. 3. Obstacles to overcoming reading difficulties (dyslexia) in class IV of Mlajah 2 Elementary School, namely the busyness of parents which results in no time to assist children in learning so students have low motivation to learn, especially reading. The inability of schools to monitor students one by one